Relationship Between Environmental Literacy With Self Efficacy in Biology Learning Class High School: Hubungan Literasi Lingkungan dengan Self Efficacy pada Pembelajaran Biologi kelas X SMA - Yakuti, YaKuti Afifah (Indonesian Journal of Science and Education, 2022)
In the era of the industrial revolution 4.0, technology is developing more rapidly, which cannot avoid large energy needs. Using large amounts of energy results in exploiting energy sources and causes environmental damage. Implementing environmental education is one of the efforts to prevent environmental damage by fostering environmental literacy. Self-efficacy beliefs are important for students to deal with situations or problems. This type of research is quantitative correlation using Pearson Product Moment (PPM) correlation data analysis. This study explains the relationship between environmental literacy and self-efficacy in learning biology class X SMA. The sampling technique in this study is simple random sampling. The total sample size is 180 students of class X MIPA at SMA Negeri 14 Semarang. The results of the calculation of the Pearson Product Moment (PPM) correlation analysis using the IBM SPSS 22 application for windows obtained a count = 0.331 and the value of Sig. = 0.007. Value of Sig. Obtained <0.05, so Ha accepted that there is a relationship between environmental literacy and self-efficacy in learning biology class X SMA.